KONTRIBUSI KECEPATAN REAKSI DAN KELINCAHAN TERHADAP KETERAMPILAN GULAT GAYA BEBAS - Juhransyah - (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2010)
Purpose of this research is to know contribution of speed reaction and mobility to skill of free-style wrestling at wrestler Mahasiswa Jurusan Pendidikan Olahraga and Kesehatan (JPOK) University Mangkurat (UNLAM) Banjarbaru. Result of research, based on result of analysis calculation hypothesis statistically relative contribution of speed reaction of 47,11 % and its effective 10,36 % to skill of free-style wrestling, relative contribution of mobility 52,89 % and its effective contribution 11,64 % to skill of free-style wrestling, relative contribution of speed reaction and mobility 100 % and his(its effective contribution 22 % to skill of free-style wrestling.